Healthy settings / Health promoting settings - Kovačević, Irena (Array, 2019)
In addition to genetic factors, human health is influ¬enced by many other exogenous factors: environ¬mental set-up, housing conditions, education, public services, social security, protection of people, etc. Health improvement and the creation of potentials for good health before health problems and vulner¬ability appear are the fundamental determinants of health promotion. The World Health Organization advocates health promotion and providing healthy surroundings that would allow the maximal expression of all human potentials (mental, physical, social, spiritual). The aim of this article was to examine the association of environmental factors that affect mental and physical health. By a series of public health pro¬grams, there is an attempt to preserve health from the earliest beginning of life – from its conceivement. Negative environmental factors present in the early phases of childhood may produce far-reaching consequences for the entire life. Critical groups include elderly people, homeless, migrants, persons with special needs and those living on the margin of poverty. The reorientation of the health system is necessary, so that its focus is moved toward the individual and community, and to strengthen the culture oriented to health and prevention, not to disease. The coop¬eration and linking inside the sector and with other sectors by the creation of partnerships and networks is unavoidable. There are many examples of the Healthy Cities project that contributed to the wellbeing of citizens on the level of city administration.